Implementation of a stereotactic body radiotherapy program for unresectable pancreatic cancer in an integrated community academic radiation oncology satellite network. (March 2021) - Augustyn, Alexander; Reed, Valerie I.; Ahmad, Neelofur; Bhutani, Manoop S.; Bloom, Elizabeth S.; Bowers, John R.; Chronowski, Gregory M.; Das, Prajnan; Holliday, Emma B.; Delclos, Marc E.; Huey, Ryan W.; Koay, Eugene J.; et al.
Highlights: PDSA methodology was used to implement a pancreas SBRT in an academic satellite network. Oncologic outcomes were favorable with no serious adverse events. This technical note provides groundwork for safe establishment of SBRT pancreas programs. Abstract: Background: With increasing interest in stereotactic body radiotherapy (SBRT) for unresectable pancreatic cancer, quality improvement (QI) initiatives to develop integrated clinical workflows are crucial to ensure quality assurance (QA) when introducing this challenging technique into radiation practices. Materials/Methods: In 2017, we used the Plan, Do, Study, Act (PDSA) QI methodology to implement a new pancreas SBRT program in an integrated community radiation oncology satellite. A unified integrated information technology infrastructure was used to virtually integrate the planned workflow into the community radiation oncology satellite network (P – Plan/D – Do). This workflow included multiple prospective quality assurance (QA) measures including multidisciplinary evaluation, prospective scrutiny of radiation target delineation, prospective radiation plan evaluation, and monitoring of patient outcomes. Institutional review board approval was obtained to retrospectively study and report outcomes of patients treated in this program (S – Study). Results: There were 12 consecutive patients identified who were treated in this program from 2017 to 2020 with a median follow-up of 27 months. The median survival was 13 months, median local failure free survival was 12 months and median progression free survival was 6 months from SBRT. There were no acute or late Common Terminology Criteria for Adverse Effects (CTCAE) version 5 toxicities ≥ Grade 3. Conclusion: We report the successful implementation of a community pancreas SBRT program involving multiple prospective QA measures, providing the groundwork to safely expand access to pancreas SBRT in our community satellite network (A – Act).